KONTEKSTUALISASI PERATURAN DAERAH KOTA BATAM TERKAIT PENCEMARAN LINGKUNGAN PERSPEKTIF SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Winsherly Tan; Indry Wulandari Irawan (Maleo Law Journal, 2021)
Law Number 32 of 2009 concerning Environmental Protection and Management is an important legal instrument in the aspect of environmental protection and management which is then manifested by the Batam City Government and related policy stakeholders in the form of legal products, namely Batam City Regional Regulation Number 4 of 2016 concerning Protection and Management of the Environment and Batam City Regional Regulation Number 4 of 2017 concerning the Implementation of Regional Health which is the commitment of the Batam City Government and related policy makers to protect, protect and preserve the environment so that it can become a good and healthy. For research in this writing, using normative research methods, which are based on written regulations, literature study that examines aspects of theory, as well as legal explanations. And the results of this study indicate that Regional Regulations related to Environmental Protection and Management as well as Health Implementation This community can encourage the achievement of the Suistainable Development Goals (SDGs).